Endogean beetles (Coleoptera) of Madagascar: deep soil sampling and illustrated overview - Andújar, Carmelo; Grebennikov, Vasily V. (Zootaxa, 2021)
This study addresses the diversity of deep soil beetles on the old continental island of Madagascar. We highlight Coleoptera as the only order of insects repeatedly occupying the deep soil (=endogean) habitat. We describe and illustrate soil flotation technique used during our fieldwork in Madagascar in December 2019. We focus on the method’s high-output and mobile technicalities. We document 51 deep soil samples, each about 20 litres in volume, taken by us in varying Malagasy localities (Andringitra, Road RN7, Ankaratra, Andasibe) and habitats (primary forest versus grassland). We provide a preliminary illustrated overview of 1,430 deep soil beetles of Madagascar sampled by us. They include representatives of Carabidae (Anillini, Reicheiina), Leiodidae, Staphylinidae (Aleocharinae, Euaesthetinae, Osoriinae, Paederinae, Pselaphinae, Scydmaeninae), Scarabaeidae, Tenebrionidae and Curculionidae. We emphasize the significant disparity between collecting 1,430 adult endogean beetles and only about a dozen of their larvae, all belonging to Scydmaeninae.